Comprehensive Analysis of Key m6A Modification Related Genes and Immune Infiltrates in Human Aortic Dissection - Yin, Fanxing; Zhang, Hao; Guo, Panpan; Wu, Yihao; Zhao, Xinya; Li, Fangjun; Bian, Ce; Chen, Chen; Han, Yanshuo; Liu, Kun (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objective: To identify the feature of N6-methyladenosine (m6A) methylation modification genes in acute aortic dissection (AAD) and explore their relationships with immune infiltration. Methods: The GSE52093 dataset included gene expression data from patients with AAD and healthy controls was downloaded from Gene Expression Omnibus (GEO) database in order to obtain the differentially expressed genes (DEGs). The differentially methylated m6A genes were obtained from the GSE147027 dataset. The differentially expressed m6A-related genes were obtained based on the intersection results. Meanwhile, the protein-protein interaction (PPI) network of differentially expressed m6A-related genes was constructed, and hub genes with close relationships in the network were selected. Later, hub genes were verified by using the GSE153434 dataset. Thereafter, the relationships between these genes and immune cells infiltration were analyzed. Results: A total of 279 differentially expressed m6A-related genes were identified in the GSE52093 and GSE147027 datasets. Among them, 94 genes were up-regulated in aortic dissection (AD), while the remaining 185 were down-regulated. As indicated by Gene Ontology (GO) functional enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses, these genes were mainly associated with extracellular matrix (ECM) and smooth muscle cells (SMCs). The seven hub genes, namely, DDX17, CTGF, FLNA, SPP1, MYH11, ITGA5 and CACNA1C, were all confirmed as the potential biomarkers for AD. According to immune infiltration analysis, it was found that hub genes were related to some immune cells. For instance, DDX17, FLNA and MYH11 were correlated with Macrophages M2. Conclusion: Our study identifies hub genes of AD that may serve as the potential biomarkers, illustrates the development the molecular mechanism of AD, and provides support for subsequent research and treatment development.